Pendampingan Penyusunan Dokumen PSETK Desa Doda Kecamatan Lore Utara Kabupaten Poso - Usuli, Sudarto; Kapuy, Holmes Rolandy; Pujiono, Pujiono; Mowidu, Ita; Wacana, Gitit I.P; Pandoyu, Ebelhart O.; Bangguna, David S.V.L (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2024)
ABSTRACTWith the program from the government so that the Village Irrigation Areas in Indonesia compile the Institutional Engineering Socio-Economic Profile (PSETK). Not all of the irrigation areas in Poso Regency are involved in the PSETK program, one of the irrigation areas that received the PSETK program is the irrigation area of Doda village. Based on D.I Doda's search and analysis results, it is known that Doda irrigation has potential land and potential farmer resources that allow for a program to increase productivity of lowland rice farming. The Doda Irrigation only has one P3A. With an active performance of 51% - 75%, this condition shows that the institutions that have been formed have quite an active role in the development and management of agricultural irrigation systems. The administration, which is poorly recorded and organized, has not made a real contribution to the community's economy. Physically, the distribution channels and buildings in D. I Doda are generally structurally damaged but can still function. This happened because of the weak awareness of the farming community to work together to clean weeds which caused the existing condition of the channel and distribution building to be closed, thus disrupting the distribution of water to the rice fields.  ABSTRAKDengan adanya program dari pemerintah agar Daerah Irigasi Desa di Indonesia menyusun Profil Sosial Ekonomi Teknik Kelembagaan (PSETK). Daerah irigasi di Kabupaten Poso tidak semuanya terlibat dalam program PSETK tersebut, salah satu daerah irigasi yang menerima program PSETK adalah daerah irigasi desa Doda. Berdasarkan penyusuran D.I Doda dan hasil analisis diketahui bahwa irigasi Doda memiliki potensi lahan dan sumberdaya petani yang potensial yang memungkinkan untuk program peningkatan produktivitas usaha tani padi sawah. Daerah Irigasi Doda hanya mempunyai satu P3A. Dengan kinerja 51 % - 75% aktif, kondisi ini memperlihatkan kelembagaan yang sudah terbentuk cukup berperan aktif dalam pengembangan dan pengelolaan sistem irigasi pertanian. Administrasi yang kurang tercatat dan tertata, belum memberikan kontribusi nyata bagi ekonomi masyarakat. Secara fisik saluran dan bangunan distribusi yang ada di D. I Doda umumnya mengalami kerusakan struktur namun masih dapat berfungsi. Hal ini disebabkan lemahnya kesadaran masyarakat petani bergotong - royong membersihkan gulma yang menyebabkan kondisi eksisting saluran dan bangunan distribusi tertutup sehingga mengganggu distribusi air ke petak sawah.